The good German - Kanon, Joseph (New York : Picador, 2002)
The bestselling author of Los Alamos and Alibi returns to 1945. Hitler has been defeated, and Berlin is divided into zones of occupation. Jake Geismar, an American correspondent who spent time in the city before the war, has returned to write about the Allied triumph while pursuing a more personal quest, his search for Lena, the married woman he left behind. When the body of an American soldier is found in the Russian zone during the Potsdam Conference, Jake stumbles on the lead to a murder mystery. The Good German is a story of espionage and love, an extraordinary recreation of a city devastated by war, and a thriller that asks the most profound ethical questions in its exploration of the nature of justice, and what we mean by good and evil in times of peace and of war.
Movie tie-in.
Originally published: New York: Henry Holt; London: Little, Brown, 2001.
Keywords: Foreign correspondents -- Germany -- Berlin -- Fiction; Berlin (Germany) -- Social conditions -- Fiction; Suspense fiction